Using ecological thresholds to evaluate the costs and benefits of set-asides in a biodiversity hotspot - Banks-Leite, Cristina; Pardini, Renata; Tambosi, Leandro R.; Pearse, William D.; Bueno, Adriana A.; Bruscagin, Roberta T.; Condez, Thais H. [UNESP]; Dixo, Marianna; Igari, Alexandre T.; Martensen, Alexandre C.; Metzger, Jean Paul (Amer Assoc Advancement Science, 2014)
Ecological set-asides are a promising strategy for conserving biodiversity in human-modified landscapes; however, landowner participation is often precluded by financial constraints. We assessed the ecological benefits and economic costs of paying landowners to set aside private land for restoration. Benefits were calculated from data on nearly 25,000 captures of Brazilian Atlantic Forest vertebrates, and economic costs were estimated for several restoration scenarios and values of payment for ecosystem services. We show that an annual investment equivalent to 6.5% of what Brazil spends on agricultural subsidies would revert species composition and ecological functions across farmlands to levels found inside protected areas, thereby benefiting local people. Hence, efforts to secure the future of this and other biodiversity hotspots may be cost-effective.